2020
DOI: 10.26740/al-uqud.v4n2.p218-234
|View full text |Cite
|
Sign up to set email alerts
|

Sharia Governance and Sustainability Reporting: The Mediating Role of Financial Performance

Abstract: Using a sample of registered Sharia Commercial Banks (BUS) in Indonesia during 2014-2017, we examine the effect of Sharia Governance on Sustainability Reporting with financial performance as a mediating variable. Our results support the idea that sharia governance (sharia supervisory board, independent commissioner, board of director's meeting and audit committee) has significant influence on the sustainability reporting. Further analysis indicates the mediating role of financial performance in the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…H4: There is a significant positive effect on environmental 5. Research conducted by Falikhatun et al (2020) shows a significant positive effect between ICG and sustainability reporting. Based on this research, the…”
Section: Research Frameworkmentioning
confidence: 96%
“…H4: There is a significant positive effect on environmental 5. Research conducted by Falikhatun et al (2020) shows a significant positive effect between ICG and sustainability reporting. Based on this research, the…”
Section: Research Frameworkmentioning
confidence: 96%
“…Several empirical studies that examined the relationship between corporate governance on capital structure and financial performance found different evidence. Research by Falikhatun et al (2020), Nomran et al (2018) and Nugraheni (2018) found evidence that Sharia Governance as measured using the Sharia supervisory board has a significant positive effect on ROA. This means that the greater the number of sharia supervisory boards, the greater the opportunity to carry out supervision and monitoring, to be able to encourage companies to increase transparency which in turn will increase customer confidence, and ultimately will improve the financial performance of Islamic Banks.…”
Section: Introductionmentioning
confidence: 99%